2009
DOI: 10.4103/0301-4738.55068
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Ahmed glaucoma valve drainage devices in cases of adult refractory glaucoma in Indian eyes

Abstract: Aim:To evaluate the efficacy of Ahmed glaucoma valve (AGV) drainage devices in cases of adult refractory glaucoma in Indian eyes.Settings and Design:Retrospective interventional case series study.Materials and Methods:Fifty two eyes of 32 patients of refractory glaucoma in the age group of 35 to 60 years who underwent AGV implantation with or without concomitant procedures from January 2003 to Jan 2007 were studied. Of these, 46 eyes (88%) had undergone filtering surgery earlier whereas remaining eyes underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
(26 reference statements)
2
11
1
1
Order By: Relevance
“…Das et al 6 reported approximately 85% success rate at 1 year and 88% was reported by Parihar et al 7 which are marginally higher than the success rate of AGV in our study (80.5%). This could be attributed to the FP8 models that were used in a small proportion of eyes in our study which fared worse than the FP7 models at the end of 1 year.…”
Section: Discussioncontrasting
confidence: 64%
“…Das et al 6 reported approximately 85% success rate at 1 year and 88% was reported by Parihar et al 7 which are marginally higher than the success rate of AGV in our study (80.5%). This could be attributed to the FP8 models that were used in a small proportion of eyes in our study which fared worse than the FP7 models at the end of 1 year.…”
Section: Discussioncontrasting
confidence: 64%
“…Evidence suggests that the use of valves have improved the short term, intermediate, and long term surgical outcomes. [71023] Our results also confirm that AGV implant surgery provided a level of success in the Omani population that is comparable to many other studies.…”
Section: Discussionsupporting
confidence: 88%
“…This matched with the results of other studies, in which researchers noted 88% and 89% of operated eyes with reduced intraocular pressure in the intermediate follow up periods. [720] In contrast, Wu et al . had reported that 59% of eyes operated for implanting AGV having ocular hypertension after six months, which were controlled by adding topical medication.…”
Section: Discussionmentioning
confidence: 99%
“…[1] and agree with their conclusions and would like to share the course of a uveitic glaucoma with intercalary staphyloma which was managed well with phacoaspiration, posterior chamber intraocular lens (PCIOL), and Ahmed glaucoma valve (AGV) implantation. Uveitic glaucoma is challenging due to the early onset and the numerous mechanisms of pathogenesis including steroid-induced intraocular pressure (IOP) elevation.…”
supporting
confidence: 59%